Handbook on the international political economy of china - Zeng, Ka 1973- (Edward Elgar Publishing, 2019)
This book examines the processes, evolution and consequences of China's rapid integration into the global economy. Through analyses of Beijing's international economic engagement in areas such as trade, investment, finance, sustainable development and global economic governance, it highlights the forces shaping China's increasingly prominent role in the global economic arena. Chapters explore China's behavior in global economic governance, the interests and motivations underlying China's international economic initiatives and the influence of politics, including both domestic politics and fore
Keywords: Außenwirtschaftspolitik; Wirtschaftspolitik; China; China / Foreign economic relations; China / Economic policy / 2000-; China / Economic conditions / 2000-; BUSINESS & ECONOMICS / International / Economics; Aufsatzsammlung